Obstructive airway disorders affecting individuals with hereditary hemorrhagic telangiectasia: A database review - Tristan Sinnatamby; Jennifer LaBranche; Maxine Farr-Jones; Tiana Fenske; Dilini Vethanayagam (PLoS ONE, 2025)
Rationale and objective Dyspnea is a common symptom with varied causes. Pulmonary vascular involvement in Hereditary Hemorrhagic Telangiectasia (HHT) includes pulmonary arteriovenous malformations (PAVMs) and pulmonary hypertension (PH), both which can result in dyspnea. Additionally, dyspnea is a common symptom in individuals with obstructive airway disorders (OADs) such as asthma, bronchiectasis and chronic obstructive pulmonary disease (COPD). These respiratory conditions are not mutually exclusive, individuals with HHT can have pulmonary vascular involvement and a concomitant OAD. However, the likelihood of this co-occurrence is not currently known. We aimed to determine the prevalence of co-occurrence to improve patient diagnosis and management. Methods We conducted a cross-sectional review of individuals seen in the Edmonton HHT Center as of July 2023 with a definite diagnosis of HHT to assess the proportion of patients with a concomitant OAD (asthma, bronchiectasis, or COPD). Results 132 patient charts were included. 55.3% had at least one identified PAVM and 28.0% had a documented OAD (asthma = 15.9%, COPD = 10.6%, Bronchiectasis = 2.3%). More importantly, 18.9% of individuals had both an OAD and a PAVM. Conclusions Dyspnea as a symptom of OADs requires specialized assessment and management. PAVMs in HHT also require specialized care, but involve different treatment approaches. It is important to identify individuals who have both HHT and an OAD to improve management which takes both OADs and pulmonary vascular disorders into account when assessing HHT patients with dyspnea. Early recognition creates better precision health and more effective care of individuals with HHT and dyspnea.